(untitled) (Libyan Journal of Ecological & Environmental Sciences and Technology, 2023)
The chemical composition of bee honey varies with the surrounding environment (botanical source and geographical origin), which reflects the nutritional value of honey. Accordingly, twenty Libyan honey samples were collected through the period 2016–2017 from different areas in Libya as the honey samples under study. Eight elements, including K, Na, Ca, Mg, Fe, Zn, Cu, and Mn, have been analyzed using electrothermal atomic absorption spectrometry. Also, statistical analysis of these elements has been performed to determine the present correlation between geographical origin and variation in locations of these elements from one sample to another. In addition, pollen grain analysis was performed for all honey samples to evaluate the botanical source of each sample and interpret the variations in elemental content (nutrition value) from one sample to another. These elements were returned in the ranges (mg/kg) as follows: K: 253.6–4675.5; Na: 41.0–588.0; Ca: 41.0–801.0; Mg: 7.2–44.05; Fe: 4.45–7.9; Zn: 1.05–7.75; Cu: 0.505–1.48; and Mn: 0.95–1.65 mg/kg. With regard to these elements, concentrations were compatible with several international honeys, with some discrimination in some samples.